A Call to Protect Common Species: Bats as a Case Study - Danilo Russo; Dina K. N. Dechmann (Conservation Letters)
ABSTRACT The ongoing biodiversity crisis highlights the need for targeted conservation efforts, yet the focus often remains on rare and endangered species. This overlooks the vital role of common species, which are the ecological backbone of ecosystems, supporting the stability and functioning of biodiversity. We argue that common species, especially their population dynamics and potential tipping points, are too often neglected and that their conservation is urgent. We illustrate this issue using bats (Chiroptera) as a model. This diverse mammalian order features key ecosystem service providers, including insectivores, pollinators, and seed dispersers. Bats are sensitive to anthropogenic pressures, and many species, including common ones, face population declines and the impact of ecosystem disruption. Research and conservation must urgently be expanded to include common species. Through case studies, we demonstrate how common bat species are indicators of environmental changes and the urgent need to monitor their populations. We provide recommendations for improving research, enhancing conservation policies, and adopting a more inclusive framework acknowledging the indispensable role of common species in ecosystem services and biodiversity.